LAKON PERTUNJUKAN WAYANG GOLEK PURWA DALAM KONTEKS FALSAFAH KEHIDUPAN MASYARAKAT SUNDA - Cecep Kusnendi (LP2M ISBI Bandung, 2018)
Wayang Golek is an art that has lived for centuries. As a cultural product, Wayang golek is full of the aesthetic-philosophical values of the life of the Sundanese people. These aesthetic-philosophical values are infact explicitly contained in their stories, both from the Ramayana epics, as well as from the Mahabarata epics. These educational values should be absorbed easily if the conditions of the Sundanese people are quite conducive today. The Sundanese people are now being swayed by the proliferation of